(untitled) (Genitri: Jurnal Pengabdian Masyarakat Bidang Kesehatan, 2024)
Adolescence is a period of an individual’s life with various changes ranging from physical, psychological, and social interaction development. Adolescence is vulnerable to health problems. Health education regarding sexuality in adolescents is very much needed to provide knowledge to adolescents about healthy reproduction. The health information provided is of course adjusted to age. Health education is delivered to ensure that teenagers understand and take responsibility for their reproductive health. The percentage of child marriage cases is increasing, according to data from the Direktorat Jenderal Badan Peradilan Agama, the majority of child marriages are caused by pregnancies out of wedlock, so parents need to apply for marriage dispensation. Therefore, the target of the marriage-age maturation program is aimed at junior high school/high school. This community service aims to promote healthy reproduction for teenagers to prevent child marriage. Community service activities were carried out in February 2024 and were attended by 28 class X students at SMA Bhinneka Karya 2 Boyolali. The results of the activity show that students are enthusiastic about participating in health education regarding healthy reproduction during adolescence as a means of increasing knowledge and self-awareness in maintaining individual health. The output resulting from this community service activity is that students experience increased knowledge and self-awareness about the importance of maintaining reproductive health. It is hoped that teenagers will have independence in optimizing their health and educating their peers to maintain reproductive health.